PERAN LEMBAGA PEMBERDAYAAN MASYARAKAT DALAM MENINGKATKAN PENDAPATAN IBU RUMAH TANGGA DI KECAMATAN CINA KABUPATEN BONE SULAWESI SELATAN - Marzuki, Sitti Nikmah (An - Nisa`, 2014)
Women is associated with domestic or job functions related to housework everyday. On the other hund women ore able to do o good job of domestic work and work outside the home to supplement the farnily income. The success doing the above role, certainly not an eilsy thing, because it takes o long process and the right to raise the willingness and effort to always learn to realize better condition, One af the success of a nation can be seen from the success of women in diving role, including in creating a generation of educated and nurtured well which then can have an impact on improving the local economy. The role of community development organiza-tions include financial assistance and training to improve kualitis life skills and empowerment in education. With the empowerment are scattered in several villages, allowing the housewife could have additional income from the empowerment.